BEING IS A FUNDAMENTAL CATEGORY OF PHILOSOPHY - Arislanbaeva Zoya Ernazarovna (Research Parks Publishing LLC, 2020)
This article analyzes being as a fundamental category of philosophy. Forms of existence are considered. The views of thinkers have been critically discussed.